2021
DOI: 10.1002/cctc.202100132
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Fe−N−C Electrocatalyst with Atomically Dispersed FeN4 Sites for the Oxygen Reduction Reaction

Abstract: Atomically dispersed Fe−N−C electrocatalysts have displayed excellent catalytic performances towards the oxygen reduction reaction (ORR), while the identification of the genuine active sites remains a challenge. Herein, we report a Fe−N−C electrocatalyst of FeSA/HNPC featuring single‐atomic FeN4 sites on hierarchically N‐doped porous carbon (HNPC), which shows a very competitive ORR activity in alkaline solution even at a low electrocatalyst loading of 0.2 mg cm−2 on the working electrode. A comparison of ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…As stated previously, the lone-pair electrons of pyridine N and pyrrolic N could pose as the metal-coordination sites for the formation of pyridine-Nx-Fe and pyrrole-Nx-Fe . Therefore, there would be some contribution of FeNx in the N 1s signals of pyridine N and pyrrolic N, and FeNx sites have been widely recognized as the major active sites for Fe–N–C electrocatalysts . The Fe 2p XPS spectrum of Fe/RNC was deconvoluted with six peaks attributed to Fe 2+ (709.9 and 723.5 eV), Fe 3+ (713.1 and 726.7 eV), and satellite peaks (717.3 and 730.9 eV).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As stated previously, the lone-pair electrons of pyridine N and pyrrolic N could pose as the metal-coordination sites for the formation of pyridine-Nx-Fe and pyrrole-Nx-Fe . Therefore, there would be some contribution of FeNx in the N 1s signals of pyridine N and pyrrolic N, and FeNx sites have been widely recognized as the major active sites for Fe–N–C electrocatalysts . The Fe 2p XPS spectrum of Fe/RNC was deconvoluted with six peaks attributed to Fe 2+ (709.9 and 723.5 eV), Fe 3+ (713.1 and 726.7 eV), and satellite peaks (717.3 and 730.9 eV).…”
Section: Resultsmentioning
confidence: 98%
“…49 Therefore, there would be some contribution of FeNx in the N 1s signals of pyridine N and pyrrolic N, and FeNx sites have been widely recognized as the major active sites for Fe−N−C electrocatalysts. 50 The Fe 2p XPS spectrum of Fe/RNC was deconvoluted with six peaks attributed to Fe 2+ (709.9 and 723.5 eV), Fe 3+ (713.1 and 726.7 eV), and satellite peaks (717.3 and 730.9 eV). The appearance of both Fe 2+ and Fe 3+ species was in agreement with the reported results of Fe 2p XPS in other Fe−N−C catalysts.…”
Section: Synthesis Of Fe−n−c 3d Nanorod Network Catalysts By Amentioning
confidence: 99%
“…Based on distance between the peak tip near the Fermi level and the Fermi level, and other factors such as the peak, the results show that the PDOS with Fe-N 4 @G at the Fermi level is significantly higher than that of other catalysts, indicating that Fe-N 4 @G has stronger adsorption capacity and promotes ORR reaction, which is consistent with the theory. 33,34 Figure 4 shows energy profiles of Pt, Fe, Co, Pd, Ni-N 4 @G for ORR, obtaining the four-step free energy gradient of M-N 4 @G catalysts with respect according to △G n of each reaction step. From the gradient diagram, the magnitude of the potential determining step can be deduced.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the pore-size distribution diagram (inset of Figure S4) showed that there were more mesopores in these three samples, and with the increase in pyrolysis temperature, the pore size of the mesopores became smaller. This is presumably caused by the increasing amount of carbon nanotubes generated with increasing temperature [39]. The nitrogen adsorption-desorption isotherm curve of Fe-ZnO@ZIF-8 is shown in Figure S5.…”
Section: Morphologies and Microstructuresmentioning
confidence: 99%